Activated 4-Factor Prothrombin Complex Concentrate as a Hemostatic Adjunct for Neonatal Cardiac Surgery: A Propensity Score-Matched Cohort Study. (2nd December 2022) - Navaratnam, Manchula; Mendoza, Julianne M.; Zhang, Shiqi; Boothroyd, Derek; Maeda, Katsuhide; Kamra, Komal; Williams, Glyn D.
Abstract : BACKGROUND: Prothrombin complex concentrates are an emerging "off-label" therapy to augment hemostasis after cardiopulmonary bypass (CPB), but data supporting their use for neonatal cardiac surgery are limited. METHODS: We retrospectively reviewed neonates undergoing open heart surgery with first-time sternotomy between May 2014 and December 2018 from a hospital electronic health record database. Neonates who received activated 4-factor prothrombin complex concentrate (a4FPCC) after CPB were propensity score matched (PSM) to neonates who did not receive a4FPCC (control group). The primary efficacy outcome was total volume (mL/kg) of blood products transfused after CPB, including the first 24 hours on the cardiovascular intensive care unit (CVICU). The primary safety outcome was the incidence of 7- and 30-day postoperative thromboembolism. Secondary outcomes included 24 hours postoperative chest tube output, time to extubation, duration of CVICU stay, duration of hospital stay, 30-day mortality, and incidence of acute kidney injury on postoperative day 3. We used linear regression modeling on PSM data for the primary efficacy outcome. For the primary safety outcome, we tested for differences using McNemar test on PSM data. For secondary outcomes, we used linear regression, Fisher exact test, or survival analyses as appropriate, with false discovery rate-adjusted P values. RESULTS: A total of 165 neonates were included in the final data analysis: 86 in the control group and 79 in the a4FPCC group. After PSM, there were 43 patients in the control group and 43 in the a4FPCC group. We found a statistically significant difference in mean total blood products transfused for the a4FPCC group (47.5 mL/kg) compared with the control group (63.7 mL/kg) for PSM patients (adjusted difference, 15.3; 95% CI, 29.4–1.3; P = .032). We did not find a statistically significant difference in 7- or 30-day thromboembolic rate, postoperative chest tube output, time to extubation, incidence of postoperative acute kidney injury (AKI), or 30-day mortality between the groups. The a4FPCC group had a significantly longer length of intensive care unit stay (32.9 vs 13.3 days; adjusted P = .049) and hospital stay (44.6 vs 24.1 days; adjusted P = .049) compared with the control group. CONCLUSIONS: We found that the use of a4FPCC as a hemostatic adjunct for post-CPB bleeding in neonatal cardiac surgery was associated with a decrease in mean total blood products transfused after CPB without an increased rate of 7- or 30-day postoperative thromboembolism. Our findings suggest that a4FPCCs can be considered as part of a hemostasis pathway for refractory bleeding in neonatal cardiac surgery.